1981
DOI: 10.1007/bf00441705
|View full text |Cite
|
Sign up to set email alerts
|

Brain uptake of 11C-methionine in phenylketonuria

Abstract: The brain uptake of 11C-methionine was studied in 26 children with classical phenylketonuria; one adult was used as a control. Labelled methionine uptake in brain was first measured during a low phenylalanine diet and again one week later after a load of phenylalanine. Ten children aged 1 to 30 months were studied twice at intervals of several months. In children having a phenylalaninemia less than or equal to 0.3 mumoles . ml-1, a decrease in methionine brain uptake was observed with increasing age, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…The L- [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]leucine method is based on a compartmental model for the behavior of leucine in brain that includes bidirectional carrier-mediated transport of leucine at the bloodbrain barrier, an extracellular and multiple intracellular compartments in brain, and the possibility that unlabeled leucine from the breakdown of tissue protein can be reincorporated into tissue protein. The application of the model together with an appropriate experimental design, i.e., a pulse injection of a tracer dose of L-[1-14 C]leucine followed by a 60-min interval for clearance of the tracer from the blood and the brain, gives rise to Eq.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The L- [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]leucine method is based on a compartmental model for the behavior of leucine in brain that includes bidirectional carrier-mediated transport of leucine at the bloodbrain barrier, an extracellular and multiple intracellular compartments in brain, and the possibility that unlabeled leucine from the breakdown of tissue protein can be reincorporated into tissue protein. The application of the model together with an appropriate experimental design, i.e., a pulse injection of a tracer dose of L-[1-14 C]leucine followed by a 60-min interval for clearance of the tracer from the blood and the brain, gives rise to Eq.…”
Section: Discussionmentioning
confidence: 99%
“…The radiolabeled tracer is [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]leucine, which is used in conjunction with quantitative autoradiography to achieve spatial localization of the labeled protein in the brain for the determination of rates of protein synthesis in discrete brain regions (17). The operational equation of the method is:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The human brain is also known to be selectively vulnerable to hyperaminoacidemias based on the clinical findings in PKU (Scriver and Clow 1980). Moreover, studies using either brain scanning (Oldendorf et al 1971) or positron emission tomography (Comar et al 1981) have shown that the brain uptake of neutral amino acids such as methionine is greatly inhibited by increased blood concentrations of phenylalanine in humans. To test the hypothesis that the human BBB, like the rat BBB, has a neutral amino acid transport system with a very low Km (very high affinity) for neutral amino acids, the present studies were performed.…”
Section: Phenylalanine Transport At the Human Blood-brain Barriermentioning
confidence: 99%
“…However, when they are small and hydrophilic enough, the toxic metabolites readily diffuse out of the deficient cells and may cause even more severe damage to the brain (or to other organs) than to the liver where they first accumulate. In phenylketonuria (PKU) and in other aminoacidopathies as well, the development of the neurological symptoms obligatorily involves the transit of a toxic substance via the blood circulation [5], It is therefore tempting to take advantage of these features for the elimination of the diffusing metabolites.…”
Section: Introductionmentioning
confidence: 99%